Correlation between ratio of Nrf2/Keap1 and catalase gene expression in liver of hyperlipidemic rats after administration of 7-hydroxy-2-(4-hydroxy- 3-methoxyphenyl)-chromen-4-one - Prasetyastuti, .; Rubi, Dianandha Septiana; Pramana, Abrory Agus Cahya; Sadewa, Ahmad Hamim (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2019)
Hyperlipidemia results in excessive superoxide anion radicals that are the cause ofoxidative stress. Phytochemical compounds can reduce oxidative stress. The aim of thisstudy was to investigate the correlations between ratio of Nrf2/Keap1 and catalase geneexpression in livers of hyperlipidemic rats after administration of 7-hydroxy-2-(4-hydroxy-3-methoxyphenyl)-chromen-4-one. Twenty-four Rattus norvegicus rats, aged 8 weeks andweighing an average of 200 g were randomly divided into 6 groups i.e. Group 1 wasnormal group (N), Group 2 was hyperlipidemic rats (HL), Group 3 was hyperlipidemicrats with simvastatin (HL+SV), and Groups 4-6 were hyperlipidemic rats with 7-hydroxy-2-(4-hydroxy-3-methoxyphenyl)-chromen-4-one doses 10 mg (HL+10), 30 mg (HL+30) or 90 mg/200 g BW (HL+90), respectively, administered orally by gavages. At the end ofthe study, the rats were euthanized and the livers were used to analyze the ratio of Nrf2/Keap 1 and catalase gene expression. Nrf2/Keap1 ratio and catalase gene expressionbetween groups were analyzed by Kruskal Wallis test. Spearman’s correlation test wasused to analyze the correlations between Nrf2/Keap1 ratio and catalase gene expression.The administration of 3 different doses of 7-hydroxy-2-(4-hydroxy-3-methoxyphenyl)-chromen-4-one on hyperlipidemic rats increased catalase gene expression. There wasno correlation between ratio Nrf2/Keap1 and catalase gene expression. In conclusion,administration of 7-hydroxy-2-(4-hydroxy-3-methoxyphenyl)-chromen-4-one can improvecatalase gene expression in hyperlipidemic rats. However, there is no correlation betweenthe ratio of Nrf2/Keap1 gene expression and the catalase gene expression.